Cutaneous tuberculosis, different clinical spectrum of the same disease: the importance of pre-test probability - Carla Rosero; Lucy Baldeón; Valeria Alulema; Adriana Rueda; Lorena Vaca; Daniela Galarza; Cesar Prócel (PAGEPress Publications, 2024)
Antecedents. This report presents three cases of Cutaneous tuberculosis CTB that were diagnosed at Calderon Hospital, Quito, Ecuador. The first case was Tuberculosis verrucosa cutis (TVC) in a 44-year-old man with circinated erythematous areas with ulcerated nodules and verruciform plaques from the right lower limb to the hip. The second case was Lupus Vulgaris (LV) in a 50- year-old female with one-year history of pruritic dermatosis in the left ciliary area. The third case was Scrofuloderma in a 23-year-old man with erythematous nodules that drain caseous material at neck, thorax and axillary region. Almost all laboratory tests that were available turned out to have limitations as a diagnostic tool. Conclusion. In immunocompromised and high-risk individuals with atypical lesions, it is important to correlate clinical and epidemiological characteristics with the pretest probability in order to optimize indicators and determine or exclude out the diagnosis.